Multivariate morphometric analysis and behaviour of honeybees (Apis Mellifera L.) in the southern regions of Ethiopia - Amssalu, Argaw Bezabeh (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2003)
Morphometric and behavioural characteristics of honeybees, Apis mellifera were analysed using multivariate and bivariate statistical methods to characterise honeybees of southern Ethiopian region. A total of 33800 morphometric character measurements were taken from 2600 individual worker honeybees of 130 honeybee colonies collected at 26 sampling localities with an average inter-locality distance of 89km to determine the occurrence of morphoclusters. 117 experienced farmer beekeepers and beekeeping experts were interviewed on pre-tested questionnaire to investigate the behavioural characteristics of these honeybees in their respective areas. Morphometric characters associated with pigmentation and body size exhibited a higher discriminant power while forewing venation angles (B4, N23 and 026) lack discriminatory power to segregate honeybees in the southern Ethiopian region. Principal components and discriminant analyses using the most discriminatory morphological characters delineated four statistically distinct morphoclusters in the southern Ethiopian region: the smallest and yellow honeybees, A. m. woyi-gambella which are different from all African honeybees, occur in the western and southern lowlands; the small and yellowiest honeybees, Apis mellifera jemenitica in the eastern escarpment; the largest and darkest honeybees, Apis mellifera bandasii in the central and eastern highlands; and dark honeybees, Apis mellifera scutellata in the wet tropical forests. High intracolonial and intercolonial variances within and between the boundaries of the honeybee groups were detected. The former suggests areas of ecological instability, while the latter areas of transitional or natural hybridisation zones. These areas are characterised by transitional ecological zones having intermediate climate and physiography. Even though honeybees of the southern Ethiopian region are generally dark and small, they show a high tendency to reproductive swarming, migration and aggressiveness, great variation in pigmentation, size and behaviour were observed both within and between the groups. A. m. jemenitica honeybees have a high propensity to migration and less a tendency for reproductive swarming. A. m. bandasii and A. m. scutellata have a high inclination to reproductive swarming and the former has a lesser and the later intermediate propensity to migration. A. m. woyi-gambella honeybees have intermediate swarming and migration tendencies. These results revealed that reproductive swarming and migration are higher in resource-rich and resource-poor areas respectively. Honey plants of the central highlands of Ethiopia are predominantly herbaceous in nature and mainly grow on open and cultivated lands. The bulk of pollen collected came comparatively from few genera. Strong correlation was observed between the intensities of flowering and rainfall. Reproductive swarming and migration occur during high and low intensity of flowering respectively.
Keywords: Honeybee -- Ethiopia -- Behavior; Honeybee -- Ethiopia